Information System for Guidance on Student Practical Work Reports in the Computer Science Department of the Web-Based Information Management Study Program - Yulya Muharmi; Bambang Hermanto; Viona Almadea (Jurnal Pepadun, 2025)
The supervision of practical work (KP) reports in the Computer Science Department has traditionally been carried out manually, which often leads to several issues such as difficulty aligning schedules between students and supervisors and challenges in tracking the history of report revisions. To address these limitations, a web-based internship report supervision information system was developed to support the guidance process in an online, structured, and well-documented manner.This research adopted the Waterfall model as the system development framework, while a descriptive qualitative approach was applied during the requirements analysis and implementation phases. The system includes key features such as consultation scheduling, report submission, revision tracking, and management of user profiles and announcements. System evaluation was conducted through black-box testing and a User Acceptance Test (UAT), yielding a score of 81%, which indicates that users were generally satisfied with the system’s performance.Overall, the presence of this system improves efficiency and transparency in the supervision process and strengthens communication and progress monitoring for both students and supervisors.